Implementation of a Medicine Distribution System to Determine Health Assistance Priorities for Flood-Affected Communities in Aceh Tamiang - M. Khairul Anam; Tjut Rizqi Maysyarah Hadi; Michel Kasaf; Agusviyanda; M. Ikhsan Wibowo (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Flooding in Kasih Sayang Village, Manyak Payed District, Aceh Tamiang Regency created challenges in the distribution of health assistance, particularly in data collection, prioritizing recipients, and recording medicine distribution. This community service activity aimed to implement a medicine distribution system to support the prioritization of health assistance for flood-affected communities. The methods used included initial visits, observation, interviews, questionnaires, program implementation, and partner response evaluation. The program was carried out through the symbolic handover of medicines and medical equipment to the village midwife and village head, followed by a trial of the medicine distribution application with partners. The results showed that the application could be used properly by partners and helped make recipient data management more organized, faster, and systematic. The evaluation involving the village head, village officials, and village midwife showed an average score of 3.72, which was categorized as very high. The highest score was found in the need for a system to determine aid recipient priorities at 3.90, followed by the urgency of post-flood health assistance at 3.85. Overall, this program provided practical benefits in supporting a more orderly, transparent, and accountable management of health assistance at the village level.